Role of building owners in shaping the design of newly constructed churches - Ponomarenko, Elena V. (Opción)
The research objective is to reveal the role of building owners in shaping the design of newly constructed churches. The key approach was historical architectural analysis and integration of data from archives and field surveys. As a result, modern types of religious building owners are classified; the legal framework providing for public involvement in church building is examined. In conclusion, it is a peculiar characteristic of the modern South Urals architecture that the potent grassroots aspiration to revive the genius loci, deep-rooted ethnic traditions and culture, comes into conflict with insufficient professional expertise and experience.